THE EFFECTS OF SERVANT LEADERSHIP ON EMPLOYEE PERFORMANCE AT REGIONAL GOVERNMENT OFFICE SOUTHEAST MINAHASA - Tomigolung, Hanna Naftalia (Universitas Sam Ratulangi, 2015)
Servant leadership is relatively a new concept. The servant leadership is aspired to lead. There are five dimensions in servant leadership such as love, empowerment, trust, humility and vision. Employee performance becomes a measurement for any organization. One factor that can influence the employee performance is servant leadership. The objective of this research is to know the influence of servant leadership on employee performance. This research used quantitative method. The method used to analyze the data is the Multiple Regression Analysis. This research uses casual type of research where it will investigate the influence of servant leadership on employee performance. The population observed is the employees of Regional Government Office Southeast Minahasa with sample size as many as 50 respondents. This study reveals those the dimension of servant leadership has significant effect partially on employee performance in Regional Government Office Southeast Minahasa. Therefore, to increase employee performance of Regional Government Office Southeast Minahasa dimensions of servant leadership should be considered intensively. Keywords: employee performance, love, empowerment, trust, humility, vision